2016
DOI: 10.5114/pg.2016.61438
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant, neoadjuvant, and experimental regimens in overcoming pancreatic ductal adenocarcinoma

Abstract: Pancreatic cancer is one of the most aggressive and deadly malignancies. Despite better understanding of its biology and pathogenesis, contemporary treatment regimens are still insufficient. Along with the introduction of new treatment agents and combination therapy, the response rates are increasing, but these scores do not go with overall survival, and results are frequently conflicting. Therefore, contemporary medicine faces the challenge of expanding the knowledge base and practice on all grounds – patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 71 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive and deadly malignancies. Despite an improving understanding of its biology and pathogenesis, contemporary treatment regimens are still lacking in terms of efficacy [ 1 ]. Data from recent studies have shown that the occurrence and development of various human tumours are related to the inactivation of tumour-suppressor genes [ 2 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive and deadly malignancies. Despite an improving understanding of its biology and pathogenesis, contemporary treatment regimens are still lacking in terms of efficacy [ 1 ]. Data from recent studies have shown that the occurrence and development of various human tumours are related to the inactivation of tumour-suppressor genes [ 2 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 Despite in-depth understanding of its pathology and biology, current therapies do not increase the overall survival of pancreatic cancer patients. 2 Profound chemoresistance of pancreatic cancer has been associated with limited benefit to the patients receiving standard chemotherapy. 3 Endoplasmic reticulum (ER) is an organelle, which is mainly involved in the synthesis of protein, modification and folding.…”
Section: Introductionmentioning
confidence: 99%
“…The NGAL has been suggested as a protein playing an important role in carcinogenesis of various neoplasms and a key player in the development of different cancer types [ 10 , 11 ]. In the main part of the analysed dataset NGAL transcripts were significantly higher in most solid tumours compared to the corresponding normal tissues.…”
Section: Discussionmentioning
confidence: 99%